EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MENULIS TEKS NARASI SISWA KELA IV SD INPRES PANGGENTUNGAN UTARA KABUPATEN GOWA - Febrianti, Imel; Haslinda; Nur Khadijah Razak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem of this research is How is the effectiveness of the Problem Based Learning learning model on the ability to write narrative texts of fourth-grade students of SD Inpres Panggentungan Utara, Gowa Regency. This study aims to determine the effectiveness of the Problem Based Learning (PBL) learning model on the ability to write narrative texts of fourth-grade students of SD Inpres Panggentungan Utara, Gowa Regency. This type of research is an experimental study with a Pre-Experimental Design type with a research design used one group pretest-posttest design. The population of this study was all fourth-grade students of SD Inpres Panggentungan Utara in the odd semester of the 2025/2026 academic year and the sample in this study was saturated sampling of all fourth graders. The instruments used were assessment sheets, observation sheets and narrative text writing tests. Data analysis of this study included descriptive statistical analysis and inferential statistical analysis. The results obtained from the descriptive statistical analysis are as follows: (1) The average pretest and posttest scores are 54.81 and 70,74 (2) The average pretest frequency is 21.6% and the posttest frequency is 25.7% The results of the frequency analysis obtained: (1) The normality test on the pretest data is 0.085 and the posttest is 0.209 that the data is normally distributed (2) the results of the hypothesis test show a t count of -9.225 with a significance value (Sig. 2-tailed) of 0.000 < 0.05. Based on the results of the study, it can be concluded that the Problem Based Learning learning model is effective on the ability to write narrative texts of grade IV students of SD Inpres Panggentungan Utara.